PENGORGANISASIAN PEMAKAMAN DAN SKEMA KESEJAHTERAAN DALAM MASYARAKAT MUSLIM PERKOTAAN: STUDI KASUS DI KOTA YOGYAKARTA - Subhan Purno Aji (Jurnal Sosial Soedirman, 2018)
This paper treats the funeral organization as a welfare proxy (governance arrangement of market-state-society) in the context of a society that has undergone rationalization, secularization, medicalization, and loss of "sense" as a community. This paper limits itself to funeral organizers in Muslim communities in Yogyakarta City, Special Region of Yogyakarta Province. This paper finds that there is variation in the organization of funerals in urban communities by different institutions, ie by commercial institutions, state and religious communities. The variation illustrates the variation of welfare schemes in mortal services and/or funeral organization in urban communities.